IMPROVEMENT OF TEACHER’S ORGANIZATIONAL CITIZENSHIP BEHAVIOR THROUGH TRANSFORMATIONAL LEADERSHIP DEVELOPMENT AND INTERPERSONAL COMMUNICATIONS - Nunung Nuryani; Nandang Hidayat; Henny Suharyati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
The purpose of this study is to show Teacher’s Organizational Citizenship Behavior (OCB) that can be improved by examining variables such as Transformational Leadership and Interpersonal Communication. This study uses a survey method with a correlational approach. The number of samples used was 104 people by using proportional random sampling technique. Based on the results of the study it is concluded that: (1) there is a very significant positive relationship between the Principal Transformational Leadership and Organizational Citizenship Behavior of teachers with a simple linear regression equation Ŷ = 99.53 + 0.32 X1 and the correlation coefficient value ry.1 = 0.417. The coefficient of determination r2y.1 = 0.174 means that the Transformational Leadership (X1) contributes to the teacher's Organizational Citizenship Behavior by 17.40%, (2) there is a very significant positive relationship between Interpersonal Communication with Organizational Citizenship Behavior teachers with simple linear regression equations Ŷ = 100.44 + 0.29 X2 and the correlation coefficient ry.2 = 0.349, and the coefficient of determination r2y.2 = 0.116 which means that the contribution of Interpersonal Communication (X2) to the Organizational Citizenship Behavior of the teacher is 19.60%, (3) there is a very significant positive relationship between Transformational Leadership and Interpersonal Communication together with the Organizational Citizenship Behavior of teachers with the multiple linear regression equation Ŷ = 77.25 +0.27 X1 +0.21 X2 and the correlation coefficient value ry.12 = 0.152. The coefficient of determination r2y.12 = 0.390 means that the Principal Transformational Leadership (X1) and Interpersonal Communication (X2) together contribute to the Organizational Citizenship Behavior of teachers (Y) by 15.20%.